Eleven Guilty Men from Goredema: Parallel Justice and the Moralities of Local Administration in Northwestern Zimbabwe - Worby, Eric (Anthropologica, 2022)
In the late 1980s, at a time when the newly independent Zimbabwean state was still struggling to fortify local organs of legal and development administration, a group of male collaterals in the northwestern district of Gokwe was inventing a parallel corporate structure for purposes of limited self-governance. This article narrates the dramatic events consequent upon a case of rape and incest, using it as a point of departure to explore how spheres of local jurisdiction may be carved out and tested, and the morality of state intervention ultimately contested, by a newly imagined, if deeply patriarchal, form of civil society.